2016
DOI: 10.1002/adfm.201602333
|View full text |Cite
|
Sign up to set email alerts
|

Material‐Driven Fibronectin Assembly Promotes Maintenance of Mesenchymal Stem Cell Phenotypes

Abstract: 6563wileyonlinelibrary.com in order to maintain multipotency. When using MSCs for regenerative medicine, it is important to obtain a suffi cient number of cells that maintain pluripotency without compromising MSC senescence. [ 3,4 ] Material systems that mimic the natural niche environment of MSCs may offer an alternative to the use of complex cocktails of soluble factors used in the culture media. Previous studies show that the cell/material interface plays an essential role on MSC function and differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…FN nanonetworks on PEA promoted cell adhesion and maintenance of stem cell phenotypes in the absence of GFs [20], [39], [40], [41]. PEA driven FN nanonetworks allow efficient GF presentation and we have shown that PEA+FN+BMP-2 increased osteogenic differentiation in MSCs compared with soluble BMP-2 along with bone regeneration in a critical size defect, [22].…”
Section: Discussionmentioning
confidence: 77%
“…FN nanonetworks on PEA promoted cell adhesion and maintenance of stem cell phenotypes in the absence of GFs [20], [39], [40], [41]. PEA driven FN nanonetworks allow efficient GF presentation and we have shown that PEA+FN+BMP-2 increased osteogenic differentiation in MSCs compared with soluble BMP-2 along with bone regeneration in a critical size defect, [22].…”
Section: Discussionmentioning
confidence: 77%
“…It has been shown that the adhesion of FN on poly (ethyl acrylate) (PEA) can lead to a spontaneous organization of FN into protein networks. It has also been shown that cell-free material-induced FN fibrillogenesis influences the maintenance and differentiation of stem cells [3,92]. Furthermore, it was described that the FN network has an increased ability to store growth factors [93].…”
Section: Discussionmentioning
confidence: 99%
“…8,9,27,29,30 The most studied surface property influencing Fn conformation is the wettability: hydrohpobic surfaces induce material-driven Fn fibrillogenesis, whereas globular conformation is typical for the protein adsorbed on hydrophilic surfaces. 9,10,27,30,31 Our results are in good agreement with these previous reports. All surfaces studied by us are hydrophilic (Table S1) and the AFM analysis indeed revealed the expected formation of aggregates of different sizes on all − OH containing surfaces ( Figure 1D1− 3).…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%